EVALUATION OF BRAIN LESIONS BY MAGNETIC RESONANCE SPECTROSCOPY IN TERTIARY HOSPITALS OF FAISALABAD - Khokhar, Abdul Maajid; Ali, Rimsha; Habib, Wazooha (MNJ (Malang Neurology Journal), 2024)
Background: One of the most fascinating and intricate organs in the human body is the brain. Infectious and neoplastic lesions in brain tissues can be identified by Magnetic Resonance Imaging (MRI). Objective: This study sought to determine which Magnetic Resonance Imaging (MRI) sequence is more usually used for differentiating brain lesions and which metabolites are examined by Magnetic Resonance Spectroscopy in Tertiary hospitals of Faisalabad. This study also aimed to check the efficacy and cost-effectiveness of MRI in the detection of various brain lesions. Methods: A cross-sectional study was conducted in the Radiology Department of different tertiary hospitals in Faisalabad. The data was collected from 25 patients (aged between 25 to 70 years) via a convenient sampling technique. Data was collected by performa and analyzed by SPSS V 20. Results: Out of 25 patients; 20 were male and 5 were female. 15 patients were diagnosed with a tumor, 5 with tuberculosis infectious lesions, 3 with empyema, and 2 with a heterogenous picture of metabolites. According to the results of MRS, different metabolites are used by different hospitals for the evaluation of various brain lesions. Brain infectious and neoplastic lesions can be distinguished quite effectively using MRS, although some infectious lesions can be difficult to distinguish. Conclusion: MRI is a non-invasive technique to identify brain tumors and infectious lesions. The main metabolites in H1MRS are Choline, Creatine, and N-Acetyl Aspartate. A high Cho/Cr ratio indicates brain tumors while a low NAA/Cr ratio indicates infectious lesions. When MRS indicates a tumor, not only a brain 99mTc scan should be performed, but if necessary surgical removal of brain lesions should be preferred.